HYDROTHERMALLY GROWN ZEOLITE CRYSTALS - Durrani, S. K.; Qureshi, A. H.; Hussain, M. A.; Ahmed, N.; Qazi, N. K.; Ahmad, M. (The Nucleus, 2020)
The aluminium-deficient and ferrosilicate zeolite-type materials were synthesized by hydrothermal process at 150-170oC for various periods of time from the mixtures containing colloidal reactive silica, sodium aluminate, sodium hydroxide, iron nitrate and organic templates. Organic polycation templates were used as zeolite crystal shape modifiers to enhance relative growth rates. The template was almost completely removed from the zeolite specimens by calcination at 550 oC for 8h in air. Simultaneous thermogravimetric (TG) and differential thermal analysis (DTA) was performed to study the removal of water molecules and the amount of organic template cations occluded inside the crystal pore of zeolite framework. The ~12-13% weight loss in the range of (140-560oC) was associated with removal of the (C3H7)4N+ cation and water molecules. X-ray diffraction (XRD) analysis and scanning electron microscope (SEM) techniques were employed to study the structure, morphology and surface features of hydrothermally grown aluminium-deficient and ferrosilicate zeolite-type crystals. In order to elucidate the mode of zeolite crystallization the crystallinity and unit cell parameters of the materials were determined by XRD, which are the function of Al and Fe contents of zeolites.